Filogeografia do complexo Ischnocnema lactea e Ischnocnema holti (Anura, Brachycephalidae), sudeste do Brasil - Teixeira, Laryssa Sakayanagi [UNESP] (2015)
Among the different environments of the Atlantic forest, the high altitude areas are habitat for some endemic species of amphibians. Such species can provide evidence to test the hypothesis that mountainous environments provide barriers to the dispersion. Thus, each population can evolve independently, suffering speciation. Ischnocnema holti is found in high altitude areas of the Atlantic forest. Previous papers have shown that there is genetic divergence between samples from different locations and that there is misidentification with Ischnocnema lactea. The aims of this study were to characterize geographically the genetic diversity of Ischnocnema holti, to discuss the existence of possible new species in this complex, and to infer the historical processes involved in the diversification of Ischnocnema holti. We infer phylogenetic relationships using DNA sequence data from two mitochondrial and four nuclear genes coupled with Bayesian and Maximum Likelihood reconstructions.We estimated divergence times (tMRCA) and also used Bayesian clustering analysis. Finally, we modelled the location of suitable climate for the complex species under present-day conditions and paleoclimates (SDMs). These results indicate that populations of I. holti and I. lactea form a complex of species distributed in the tops of the mountains of the Atlantic Forest of southeastern Brazil. We found six clades supported by mitochondrial and nuclear markers (even with minor variations) and genetically divergent, however we could not resolve the relationship between them. The modeling suggests that the populations of this complex remained restricted regions of altitude at least since the Last Interglacial (LIG), although they may have had a small habitat expansion in the last Glacial Maximum. The dating of the separation of lineages also suggests an older isolation, and the separation would have occurred between 7 and 11 million years...